The Influence of Cooper and Chromium Ions on the Production of Exopolysaccharide and Polyhydroxybutyrate by Rhizobium tropici LBMP-C01 - Leonel, Tatiane Fernanda [UNESP]; Moretto, Cristiane [UNESP]; Castellane, Tereza Cristina Luque [UNESP]; da Costa, Paulo Inácio [UNESP]; Lemos, Eliana Gertrudes de Macedo [UNESP] (Springer Nature, 2019)
The influence of bivalent copper (Cu 2+ ) and hexavalent chromium (Cr 6+ ) ions on exopolysaccharide (EPS) and polyhydroxybutyrate (PHB) production by the bacterium Rhizobium tropici LBMP-C01 was investigated. The partial structure of both biopolymers produced by rhizobia were characterized, and the quantification of exoR and exoZ gene expression by real-time polymerase chain reaction (Real-Time PCR) was also investigated. Results showed that the supplementation with Cu 2+ for 144 h induced an increase in the production of EPS by 48% and PHB by 46.66% compared to the control. Expression studies revealed that the expressed exoR and exoZ genes were affected by metal ion treatment. It can be stated that this particular rhizobial strain is a future potential candidates to produce super adsorbent quite useful for soil bioremediation.
Keywords: Exopolysaccharide; Heavy metals; Polyhydroxybutyrate; Rhizobia